NEAT1 contributes to neuropathic pain development through targeting miR‐381/HMGB1 axis in CCI rat models - Xia, Lie‐Xin; Ke, Chengming; Lu, Jing‐Min (Journal of cellular physiology, 2018)
LncRNAs have been recognized as significant regulators in various diseases including neuropathic pain. Although the lncRNA NEAT1 has been reported to be involved in multiple cancers, its biological functions in neuropathic pain still remain unknown. In our present study, a chronic constriction injury (CCI) rat model was established and we found that NEAT1 was greatly upregulated in the spinal cord tissues of CCI rats. Knockdown of NEAT1 can repress neuropathic pain behaviors including mechanical and thermal hyperalgesia. In addition, NEAT1 downregulation inhibited neuroinflammation via inhibiting IL‐6, IL‐1β, and tumor necrosis factor (TNF)‐α in CCI rats. We also observed that miR‐381 was decreased significantly in CCI rats. By using bioinformatics analysis, miR‐381 was predicted to be a microRNA target of NEAT1, which indicated a negative correlation between miR‐381 and NEAT1. Inhibition of NEAT1 can induce miR‐381 expression in CCI rats, which indicated a negative correlation between NEAT1 and miR‐381. HMGB1, as a downstream target gene of miR‐381 was observed to be dramatically increased in CCI rats. miR‐381 can modulate HMGB1 expression negatively and meanwhile, NEAT1 was able to regulate HMGB1 through sponging miR‐381. Downregulation of HMGB1 can inhibit neuropathic pain behaviors which can be reversed by miR‐381 inhibitors. Taken these together, it was indicated that NEAT1 can induce neuropathic pain development in CCI rats via regulating miR‐381/HMGB1 axis. We found that knockdown of NEAT1 can alleviate neuropathic pain by increasing miR‐381 and inhibiting neuro‐inflammation in CCI rats. For another, NEAT1 can modulate HMGB1 by sponging miR‐381 in neuropathic pain. Our findings indicated that NEAT1 can serve as a treatment target in neuropathic pain.